Peningkatan Kemampuan Baca Tulis Aksara Jawa Melalui Media Pembelajaran Berbasis Game Kwartet Aksara Jawa - Sita Nuraseh; Annisa Indah Ayu; Alyna Kirana Dewi; Syerliana Nur Annisa; Fiska Petricia; Rahmat Rahmat (Society : Jurnal Pengabdian Masyarakat, 2023)
The Javanese language subject is a subject at the Elementary School (SD) level which includes learning related to Javanese literature, language, and culture. One indicator of the success of learning Javanese is that students have the ability to read and write Javanese script. Students' skills in reading and writing Javanese script are influenced by the condition of students in knowing Javanese script letters. So that students can be skilled in reading and writing Javanese script. We conducted this research to improve the ability of fifth grade students at Wirogunan 2 Public Elementary School in writing and reading Javanese script using the Javanese Script Quarted Game. This research involved 22 students of class V at SD Negeri Wirogunan 2 as research subjects. In this study, the authors used a qualitative descriptive approach. Data collection techniques used are observation, interviews, documentation, and tests. Data validity uses source triangulation, namely comparing information obtained from different sources to re-check the degree of trustworthiness of information. The results of the research explain that the learning media innovation uses this quartet game, namely the students are very enthusiastic about learning to memorize Javanese script and it is hoped that through this game over time students can memorize all forms of Javanese script. In addition, the students will be challenged and enthusiastic in memorizing the Javanese script letters, because if they have memorized all the Javanese script letters, it will be easy to win this game.